A taxonomic study of the genus Eupteryx Curtis (Hemiptera: Cicadellidae: Typhlocybinae), with description of five new records and one new species from China - Hou, Xiao-Jiao; Zhang, Ya-Lin; Huang, Min (Zootaxa, 2016)
A new species, Eupteryx (Stacla) gracilirama sp. nov. from China is described and illustrated and five species are recorded for the first time from China: Eupteryx (Stacla) janeki Dworakowska, Eupteryx (Stacla) albonigra Dworakowska, Eupteryx (Stacla) hela Dworakowska, Eupteryx (Stacla) irminae Dworakowska and Eupteryx (sensu stricto) stachydearum (Hardy). A check-list and key to all known species of Eupteryx from China are provided.